2019
DOI: 10.1128/aem.03126-18
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus Sequence Analysis, a Rapid and Accurate Tool for Taxonomic Classification, Evolutionary Relationship Determination, and Population Biology Studies of the Genus Shewanella

Abstract: The genus Shewanella comprises a group of marine-dwelling species with worldwide distribution. Several species are regarded as causative agents of food spoilage and opportunistic pathogens of human diseases. In this study, a standard multilocus sequence analysis (MLSA) based on six protein-coding genes (gyrA, gyrB, infB, recN, rpoA, and topA) was established as a rapid and accurate identification tool in 59 Shewanella type strains. This method yielded sufficient resolving power in regard to enough informativ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 44 publications
2
8
0
1
Order By: Relevance
“…Compared with the report by Fang et al . [14], the phylogeny of S. algae in our study was consistent with the topological structure and evolutionary relationship of the phylogenetic tree constructed by MLSA method.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Compared with the report by Fang et al . [14], the phylogeny of S. algae in our study was consistent with the topological structure and evolutionary relationship of the phylogenetic tree constructed by MLSA method.…”
Section: Discussionsupporting
confidence: 84%
“…haliotis has been recently identified as a synonym of S. algae by the previous research [14]. The 12 morphologically well-characterized strains in this study were initially identified by API 20E and 16S rRNA gene analysis.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, the low frequency of polymorphisms and the absence of positive selection of the studied genes suggest a nearly neutral mechanism for their evolution. Thus, all the selected genes showed similar features and, therefore, could be applied in an MLSA approach, as occurred in other bacterial models [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Los resultados confirman que la combinación de métodos para la identificación de bacterias es lo más adecuado. Por un lado, los métodos tradicionales de identificación de bacterias aun siendo menos sensibles, son ampliamente utilizados ya que brindan información sobre la morfología y la actividad de las cepas en cuestión (Fang et al, 2019). Por otro la práctica recomienda complementar los resultados de la caracterización fisiológica y bioquímica con los análisis filogenéticos de secuencias multilocus para la identificación de bacterias luminiscentes (Ast & Dunlap, 2005;Thompson, et al, 2005;Delgado et al, 2017).…”
Section: Discussionunclassified